2016
DOI: 10.1038/srep24835
|View full text |Cite
|
Sign up to set email alerts
|

The Tumour Response to Induction Chemotherapy has Prognostic Value for Long-Term Survival Outcomes after Intensity-Modulated Radiation Therapy in Nasopharyngeal Carcinoma

Abstract: The prognostic value of the tumour response to induction chemotherapy (IC) for long-term survival outcomes after intensity-modulated radiation therapy in nasopharyngeal carcinoma (NPC) remains unknown. We retrospectively reviewed 1811 consecutive patients with newly diagnosed NPC treated using IMRT, and 399 eligible patients with pre- and post-induction chemotherapy magnetic resonance images were recruited. The clinicopathological features of patients with different tumour responses were compared using the Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 32 publications
2
53
0
Order By: Relevance
“…This should be attributed to insufficient follow-up and the small sample in each group, which could result in a low testing power. The effective response rate (CR plus PR) to the TPF regimen in the current study was 90.9%, which was consistent with the results of our retrospective study (91%), 27 but was much higher than that in the study by Liu et al in which the PF regimen was used (67.6%). 22 The main purpose of using NACT in clinical practice was to eliminate micrometastasis before radical IMRT and therefore improve OS for patients with advanced NPC.…”
Section: Discussionsupporting
confidence: 92%
“…This should be attributed to insufficient follow-up and the small sample in each group, which could result in a low testing power. The effective response rate (CR plus PR) to the TPF regimen in the current study was 90.9%, which was consistent with the results of our retrospective study (91%), 27 but was much higher than that in the study by Liu et al in which the PF regimen was used (67.6%). 22 The main purpose of using NACT in clinical practice was to eliminate micrometastasis before radical IMRT and therefore improve OS for patients with advanced NPC.…”
Section: Discussionsupporting
confidence: 92%
“…revealed that the unsatisfactory tumor response after induction chemotherapy (stable disease or disease progression) could predict poor prognosis for patients with advanced-stage NPC (locoregional relapse-free survival,PFS) [23]. However ;an another trial concluded that the overall tumor response after induction chemotherapy was an independent prognostic factor for disease-free-survival , OS and locoregional recurrence free survival [24].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, radiotherapy has been widely accepted as a first-line and standard treatment for advanced NPC, by providing the superior dose of distributions and the better tolerated on NPC patients [25][26][27]. The more precise the radiation technique becomes the more rigid the requirements are to precisely delineate the tumor.…”
Section: Discussionmentioning
confidence: 99%